FACTORS OF CRITICAL SUCCESS OF THE STAVROPOL STATE AGRARIAN UNIVERSITY - Vladimir I. Trukhachev (Высшее образование в России)
The article highlights the University strategic objectivesand the target results of the activities, which the University should strive for to increase the competitiveness and achieving success at the market of educational services. The necessary conditions to ensure the competitiveness in agrarian education are the acceleration of growth rate, accretion of resource potential, integration of different levels of agrarian education as well as retention of the originality of educational traditions. Special attention is paid to the factors promoting realization of the University mission.